Acute simultaneous development of brain tumour–like lesion and demyelinating polyneuropathy in a patient with chronic relapsing myelitis. (April 2018) - Puthenparampil, Marco; Terrin, Alberto; Federle, Lisa; Gizzi, Matteo; Perini, Paola; Gallo, Paolo
Combined central and peripheral demyelination (CCPD) is a rare chronic inflammatory disorder of the nervous system. We describe the case of a patient with a history of recurrent myelitis that acutely and simultaneously developed a brain tumour–like lesion and a sensitive-motor demyelinating polyneuropathy. The diagnosis of CCPD was supported by a detailed diagnostic workup. Up to date, no similar cases have been reported in the literature.